" Israel" Colonial Settlement in Palestine after 1967 (Study in Political geography) (Journal of Libya for geographical studies, 2023)
Under the banner of "Peace Agreement" signed at Oslo 1993 between POLP  and " Israel Gouverment,"Israel continues   applying  the Zionist  stratigy established  at the end of 19thcentury which  is based on : seize the land  in Palestine by different means (more than70% of total  area  of West Bank of Jordan river and control 85% of water and natural  resources    according to the  Agreement, encourage  jewish  emigration  to Palestine commets massacres  against Palestinians, destroys  their homes  and the construction of different kinds of  jewish  which increase from 140settlementsin 1993(Agreement Year)  to  461 in 2019 ,the total jewish  settlers increases from  268756 persons to  688262 p. or more  during the same period , the demographic balance  in Jerusalem became  beneficial to "Israel".    And so, the density of  colonial settlements in West bank  and judaizing Jerusalem ,the target of  Oslo Agreement   (establishment of the free state of Palestine, where the capital will be Est Jerusalem) became impossible..